TEACHING ENGLISH FOR SPECIFIC PURPOSES AND TEACHER TRAINING - Morena Bracaj (European Scientific Journal, ESJ, 2014)
The need for a lingua franca of science, technology, education, and business has led to the worldwide demand of English for Specific Purpose (ESP). The field of ESP has rapidly developed recently to become a major part in English language teaching and research. Therefore, the needs to understand the requirements of other professions and willingness to adapt to these requirements make a specific group of learners prepare differently from those learning general English, because they need English for specific purposes rather than using it in daily life. Thus the ESP approach provides opportunities to the learners to acquire English naturally, which means that, by working with language in a context that they comprehend and find interesting. But, what is the situation in Albania? Are the university classes in Albania applying this approach and what efforts are they making about ESP application, since students are in need of learning not only English for general purposes. Therefore, this paper aims to discuss some basic concepts of the 'English for Specific Purposes' (ESP) approach to language teaching, types of ESP, the ways how ESP teachers should be trained so that they can be professionals an well-prepared to meet learners` needs, and lastly a comparison is made between the “General English” teacher and the so-called ESP practitioner proposed by Dudley- Evans and St. John under the headings of teacher, collaborator, course designer and materials provider, researcher, and evaluator.